The Effect of a Speed Reading Course on the Reading Comprehension of Impulsive vs. Reflective Learners - Aroo, Gopalan; Nimehchisalem, Vahid (2023)
The goals of Asia TEFL are to promote scholarship, disseminate information, and facilitate cross-cultural understanding among persons concerned with the teaching and learning of English in Asia. In order to accomplish this, Asia TEFL will pursue the following goals: 1. To link ELT professionals in joint research on issues and concerns regarding English teaching and learning in the Asian context. 2. To publish an academic journal, The Asia TEFL Journal, as an internationally recognized journal in the field of English language teaching. 3. To host conferences and seminars addressing important issues concerning ELT in Asia. 4. To develop proficiency guidelines and assessment methods designed for the needs of the Asian context. 5. To develop programs for Asian learners and teachers of English to build their English language proficiency and cultural understanding and provide them with the skills required to be efficient English teaching professionals.